Time spent by Brazilian students in different modes of transport going to school: changes over a decade (2001-2011) - Kelly Samara Silva; Adair da Silva Lopes; Rosane Carla Rosendo da Silva; Filipe Ferreira Costa; Maria Alice Altenburg de Assis; Markus Vinicius Nahas (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
To examine changes in the time spent in each mode of transportation used for going to school by gender and age among adolescents from Santa Catarina State, Brazil. Two school-based surveys were performed in 2001 (N = 5,028) and 2011 (N = 6,529) in high school students (15-19 years old). The mode of transportation (on foot; by bicycle; by bus; car/motorcycle) and the time spent for commuting to school were assessed. Active commuting increased for short trips in both genders (male: 25.1% to 36.7%; female: 18.8% to 29.2%) and in all ages (15-16 years: 21% to 32.7%; 17-19 years: 21.9% to 32.4%), and declined for longer trips in males (30.5% to 21.9%) and in 15-16 years old students (25.7% to 34.7%). Car/motorcycle use has doubled for short trips in males (38.1% to 65.9%) and in 17-19 years old students (37.7% to 62.7%), while the use of buses remained stable in both genders. Our findings contribute to discussions on public policy focusing on the design of safe environments to promote active commuting to schools, particularly to decrease the use of motorized transport for short trips.